Hematospermia and Cloacogenic Transitional Cell Carcinoma: A Twist on Significance and Meaning - Alex M. Hennessey; Jessica M. Clement; Faripour Forouhar; John A. Taylor (Case Reports in Urology)
A 52-year-old gentleman presented with recurrent hematospermia. Further history revealed recent onset of constipation and difficulty voiding. Rectal examination revealed a firm, polypoid mass and colonoscopy showed suspicious, ulcerated lesions of the rectal mucosa with narrowing of the rectal vault. Pathology demonstrated transitional cell carcinoma of the rectum. While transitional cell carcinoma is a common genitourinary cancer, its presence in the anus and rectum is exceedingly rare. Furthermore, hematospermia is generally not associated with malignancy. This case is a remarkable example of two pathologic processes presenting in rare form and underscores the value of a thorough investigation of hematospermia when associated with other clinical symptoms.